2019
DOI: 10.1158/2326-6066.cir-18-0940
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Interferon-γ Increases MHC Class I Expression and T-cell Infiltration in Cold Tumors: Results of a Phase 0 Clinical Trial

Abstract: Interferon-g (IFNg) has been studied as a cancer treatment with limited evidence of clinical benefit. However, it could play a role in cancer immunotherapy combination treatments. Despite high expression of immunogenic cancer-testis antigens, synovial sarcoma (SS) and myxoid/ round cell liposarcoma (MRCL) have a cold tumor microenvironment (TME), with few infiltrating T cells and low expression of major histocompatibility complex class I (MHC-I). We hypothesized that IFNg treatment could drive inflammation in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 26 publications
3
63
0
1
Order By: Relevance
“…We previously showed that both MHC expression and T-cell infiltration can be increased using systemic IFN-γ and thus could improve the efficacy of ACT for SS. 18 IFN-γ likely also increases programmed death-ligand 1 (PD-L1) expression in SS tumors, and attempts to combine IFN-γ with programmed cell death protein 1 (PD-1) inhibition are ongoing. However, our results show that novel combinations of immunotherapeutic regimens must be explored cautiously, even when using treatments with well-established safety profiles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that both MHC expression and T-cell infiltration can be increased using systemic IFN-γ and thus could improve the efficacy of ACT for SS. 18 IFN-γ likely also increases programmed death-ligand 1 (PD-L1) expression in SS tumors, and attempts to combine IFN-γ with programmed cell death protein 1 (PD-1) inhibition are ongoing. However, our results show that novel combinations of immunotherapeutic regimens must be explored cautiously, even when using treatments with well-established safety profiles.…”
Section: Resultsmentioning
confidence: 99%
“…8 However, treatment of patients with SS with systemic interferon gamma (IFN-γ) increased MHC expression and increased T-cell infiltration in matched tumor biopsies in a phase 0 clinical trial. 9 Here we describe a pilot study integrating weekly IFN-γ with ACT in the context of high-dose cyclophosphamide (HD Cy)based lymphodepletion and low-dose IL-2. While the first patient (IFN#1) had an impressive regression of pulmonary tumors, the second patient (IFN#2) developed a fatal histiocytic myocarditis.…”
Section: Introductionmentioning
confidence: 99%
“…The administration of IFNs might effectively counteract HLA class I down-regulation in cancer cells by boosting the presentation of tumor specific-associated antigens [ 254 , 255 , 256 , 257 ]. A phase 0 clinical trial showed that systemic administration of IFN-γ increases not only HLA class I expression on tumor cells, but also T-cell infiltration in cold tumors [ 258 ] IFN-mediated up-regulation of HLA class I derived peptide complexes occurs via activation of the Jak/STAT pathway which induces the binding of IRFs to ISRE motifs located in HLA class I promoter region [ 107 , 254 ]. In addition, IFN-γ-mediated HLA class I derived peptide complex up-regulation is also associated to an increased histone demethylation and acetylation of APM genes in the MHC locus, particularly of histone H3 in TAP1 promoter locus [ 259 ].…”
Section: Restoring Hla Class I Expression As a Novel Therapeutic Smentioning
confidence: 99%
“…More recently, interest in IFN has resurged as investigators have uncovered possible synergy with other treatments and anti-tumoral effects. As an example, it has recently been shown that systemic subcutaneous injection of IFN in cancer patients with synovial sarcoma, a type of cold tumor, increases T cell infiltration within tumors (34).…”
Section: Discussionmentioning
confidence: 99%